kreasi Alama KREASI ALAM: WORKSHOP POCH BAG ECOPRINT SEBAGAI EDUKASI LINGKUNGAN BAGI SISWA SD AIR TENANG: Ecoprint, Edukasi Lingkungan, Pouch Bag, Siswa SD, Workshop - Novysa Basri; Novianti Novianti; Annisa Nabila; Putri Ariska; Afkar Afkar; Rahmi Hayati; Wahyudi Wahyudi (LPPM Universitas Almuslim, 2026)
Environmental issues stemming from textile waste and the use of synthetic dyes are on the rise, creating a need for eco-friendly alternatives in fabric production. Ecoprinting—a technique for printing natural patterns using plant materials—offers a solution that also serves as a medium for environmental education for elementary school students. However, its application at the elementary school level remains limited. Therefore, this community service initiative, conducted through a workshop, aims to introduce students at SD Air Tenang to ecoprinting and train them in creating ecoprinted pouches, thereby fostering early environmental awareness. The program employed a combination of awareness-raising and hands-on training. Activities began with an explanation of basic ecoprinting concepts, followed by a demonstration of the